Abnormal F-18 Fluorodeoxyglucose Uptake of the Lung in Immunocompromised Lymphoma Patients in Complete Remission: Report of Two Cases and Revision of Literature. (September 2013) - Conticello, C.; Vetro, C.; Romano, A.; Amato, G.; Schinocca, L.; Cosentino, S.; Ippolito, M.; Giustolisi, R.; Di Raimondo, F.
Limited data suggest that F-18 fluorodeoxyglucose (FDG) positron emission tomography (PET) may have a role in diagnosing infection. Here we present two cases of lymphoma patients in complete response (CR) who presented during follow-up dry cough and fever. Physical examination and serum evaluations were negative for lymphoma while whole body FDG-PET showed lung uptake which posed a differential diagnosis between relapse of lymphoma and an atypical pneumonia due to persistent lymphopenia. In both cases, cytology examination of sputum suggested Pneumocystis Jiroveci pneumonia (PJP). After appropriate antibiotic treatment, the follow-up examination showed complete resolution of the lung changes revealed by FDG-PET. False-positive results on FDG-PET were supposed to be due to the high uptake of FDG in non-neoplastic inflammatory cellular elements such as macrophages and lymphocytes. Our findings suggest that in cases of FDG-PET positive images in immunocompromised patients with previous hematologic disease, caution must be used, and differential diagnosis might include infections such as PJP in addition to relapse of disease.